Adjustment and monitoring of parameters of the gamma-ray detecors used in the experiments with the impulse accelerator IDM-20; Современные техника и технологии; Т. 3 - Valiyarova A. R. (Физические методы в науке и технике, 2014)
Заглавие с титульного экрана